Injectable hydrogel microbeads for fluorescence-based in vivo continuous glucose monitoring - Shibata, Hideaki (National Academy of Sciences, 2010)
Fluorescent microbeads hold great promise for in vivo continuous glucose monitoring with wireless transdermal transmission and long-lasting activity. The full potential of fluorescent microbeads has yet to be realized due to insufficient intensity for transdermal transmission and material toxicity. This paper illustrates the highly-sensitive, biostable, long-lasting, and injectable fluorescent microbeads for in vivo continuous glucose monitoring. We synthesized a fluorescent monomer composed of glucose-recognition sites, a fluorogenic site, spacers, and polymerization sites. The spacers are designed to be long and hydrophilic for increasing opportunities to bind glucose molecules; consequently, the fluorescent monomers enable high-intensive responsiveness to glucose. We then fabricated injectable-sized fluorescent polyacrylamide hydrogel beads with high uniformity and high throughput. We found that our fluorescent beads provide sufficient intensity to transdermally monitor glucose concentrations in vivo. The fluorescence intensity successfully traced the blood glucose concentration fluctuation, indicating our method has potential uses in highly-sensitive and minimally invasive continuous blood glucose monitoring.